Hydatid cyst of the submandibular region (KYAMC Journal, 2017)
Hydatid cyst is caused by larval stage of Echinococcus parasite, mainly/largely by E. granulosus. It usually involves one organ. It may affect many organs also. Hydatid cyst of the head and neck region is uncommon and involvement of submandibular region is very rare. Here we present a case of left submandibular region hydatid cyst. This patient is an elderly gentleman of age 61 years from Soydabad, Sirajgonj. He noticed a painless peanut size swelling in his left submandibular region 5 years back. It had started increasing in size for last 4 months and become cricket ball size. Examination revealed a soft, nontender lump in that region. Skin and subcutaneous tissues are free of lump adherence. Chest X-ray was unremarkable. CT Scan showed a benign cystic swelling. Excision was performed and pathological examination revealed a hydatid cyst.KYAMC Journal Vol. 5, No.-1, Jul 2014, Page 480-483